Segmentasi, Targeting, dan Positioning Terhadap Loyalitas Pelanggan Produk Toko Logo di Plaza Andalas Kota Padang - Milastri Sapalakai; Febsri Susanti (Jurnal Bintang Manajemen, 2023)
Loyalty is the most important aspect for a company to maintain its extension in order to maintain and attract other customers. One way that can be done in building customer loyalty is to establish good relationships with customers. Having loyal customers is the main goal of every company. This study aims to examine customer loyalty, segmentation,targeting and positioning on consumer loyalty to logo shop product plaza andalas Padang products. This research is a quantitative research, the population in this study is buyers from February to June as many as 277 buyers. The sample collection technique used in this study was Accidental Sampling, which is a sampling technique based on chance, or anyone who happens to meet a researcher who can be used as a sample using the slovin formula, the number of samples in this study was 100 people. Data analysis techniques using instrument tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results of this study indicate that product quality, testimonials, and endorsements have a positive and significant effect on consumer loyalty to logo shop product plaza andalas Padang products.